If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5 + 2t) = 9(2 + t) (5 * 4 + 2t * 4) = 9(2 + t) (20 + 8t) = 9(2 + t) 20 + 8t = (2 * 9 + t * 9) 20 + 8t = (18 + 9t) Solving 20 + 8t = 18 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. 20 + 8t + -9t = 18 + 9t + -9t Combine like terms: 8t + -9t = -1t 20 + -1t = 18 + 9t + -9t Combine like terms: 9t + -9t = 0 20 + -1t = 18 + 0 20 + -1t = 18 Add '-20' to each side of the equation. 20 + -20 + -1t = 18 + -20 Combine like terms: 20 + -20 = 0 0 + -1t = 18 + -20 -1t = 18 + -20 Combine like terms: 18 + -20 = -2 -1t = -2 Divide each side by '-1'. t = 2 Simplifying t = 2
| 39.75+9.50*h=115.75 | | X/5+9=4-1 | | 4x+6=-1+5x | | u+3/7=6 | | X^5+9=4-1 | | x(12x+20)=25 | | -(1.2x+7)+1.5x= | | 6.5-y=5.06 | | 7/9w=56 | | 2x+3=3x-9 | | 9x+x=14+6 | | x/5.09=0 | | 8r-30r+18=0 | | 5x+8=6x+8 | | -5(v-3)=-30 | | x(8x+6)=5 | | 49m-7= | | d/3-10=-2 | | 5+6x+6x=77 | | 50-e=29 | | X+(12x-1)= | | 2/3+4x/5=11/20 | | 5+12=77 | | x(3x+1)=2 | | 2(4y-2)=60 | | 4(x+3)-18=3(x+7) | | y=-33x-4 | | 63=10x+3 | | 15+1/4p=2 | | p^2-2p=0 | | x+1+x=19 | | 25x^2+9y^2=225 |